Media Pembelajaran Sistem Pengoperasian Simulasi Perakitan PC Berbasis Augemented Reality - Raniyah Ayulestari; Suci Inayah (Universitas Harapan Medan, 2026)
Learning Media PC assembly simulation operating system based on Augmented Reality PC assembly simulation based on Augmented Reality (AR) is an innovative learning media to understand computer operating systems. By utilizing AR technology, users can learn about components and the PC assembly process interactively and in-depth. Main Features of AR Simulation 3D Visualization Displays PC components such as Motherboard, CPU, RAM, and storage devices in three dimensions. Users can rotate and zoom in on objects to see their details. Interactive Guide Provides clear step-by-step instructions for each assembly stage using text to explain the function of each component. The assembly process simulation allows users to perform virtual assembly by combining components in real-time. Conclusion Augmented Reality-based PC assembly simulation is an effective learning media to understand computer operating systems. With interactive features and attractive visualizations, this simulation not only enhances students' understanding but also prepares them for real-world practice. The use of AR in education opens up new opportunities for more innovative and engaging learning methods